The Effect of Problem Based Learning (PBL) Learning Model on Problem Solving Ability and Mathematics Disposition of Class X Students of Private Vocational School Aviation Pulau Berayan Darat Medan - Karo, Nur Hidayah Br.; Asmin, Asmin; Nasution, Hamidah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study examines the influence of the Problem Based Learning (PBL) learning model on the problem solving ability and mathematical disposition of grade X students of the Private Aviation Vocational School of Berayan Island Darat Medan. Using a quasi-experimental approach with two groups, namely the experimental group taught using the PBL model and the control group taught using conventional learning, this study aims to analyze the effectiveness of PBL in improving students' problem solving skills and mathematical disposition. Data was collected through problem solving ability tests (pretest and posttest) and mathematical disposition questionnaires during the even semester of the 2024/2025 school year. The results of the two-track ANOVA analysis with a significance level of 0.05 showed that the PBL learning model had a significant influence on students' problem solving ability (F=13,669; sig.=0.000<0.05). In addition, the mathematical disposition of students was also significantly influenced by the PBL model (F=17.041; sig.=0.000<0.05). However, this study did not find any interaction between the PBL learning model and mathematical early ability (KAM) in influencing problem solving ability (F=2.114; sig.=0.131>0.05) or students' mathematical disposition (F=0.454; sig.=0.637>0.05). This indicates that the PBL model exerts influence independently without being influenced by the student's KAM. These findings suggest that PBL models can effectively improve students' problem solving abilities and mathematical dispositions, regardless of their initial ability level, as well as provide a more engaging and meaningful learning experience in mathematics learning.